Recent Advances in Anhydrous Solvents for CO2 Capture: Ionic Liquids, Switchable Solvents, and Nanoparticle Organic Hybrid Materials - Park, Youngjune; Lin, Kun-Yi Andrew; Park, Ah-Hyung Alissa; Petit, Camille (Frontiers in Energy Research, 2015)
CO2 capture by amine scrubbing, which has a high CO2 capture capacity and a rapid reaction rate, is the most employed and investigated approach to date. There are a number of recent large-scale demonstrations including the Boundary Dam Carbon Capture Project by SaskPower in Canada that have reported successful implementations of aqueous amine solvent in CO2 capture from flue gases. The findings from these demonstrations will significantly advance the field of CO2 capture in the coming years. While the latest efforts in aqueous amine solvents are exciting and promising, there are still several drawbacks to amine-based CO2 capture solvents including high volatility and corrosiveness of the amine solutions as well as the high parasitic energy penalty during the solvent regeneration step. Thus, in a parallel effort, alternative CO2 capture solvents, which are often anhydrous, have been developed as the third-generation CO2 capture solvents. These novel classes of liquid materials include ionic liquids, CO2-triggered switchable solvents (i.e., CO2-binding organic liquids, reversible ionic liquids), and nanoparticle organic hybrid materials. This paper provides a review of these various anhydrous solvents and their potential for CO2 capture. Particular attention is given to the mechanisms of CO2 absorption in these solvents, their regeneration and their processability – especially taking into account their viscosity. While not intended to provide a complete coverage of the existing literature, this review aims at pointing the major findings reported for these new classes of CO2 capture media.